Ultrasonic Characterization of the Upper Trapezius Muscle in Patients with Chronic Neck Pain - Turo, Diego (Ultrason Imaging, 2013)
Myofascial trigger points (MTrPs) are palpable, tender nodules in taut bands of skeletal muscle that are painful on compression. MTrPs are characteristic findings in myofascial pain syndrome (MPS). The role of MTrPs in the pathophysiology of MPS is unknown. Localization, diagnosis, and clinical outcome measures of painful MTrPs can be improved by objectively characterizing and quantitatively measuring their properties. The goal of this study was to evaluate whether ultrasound imaging and elastography can differentiate symptomatic (active) MTrPs from normal muscle. Patients with chronic (>3 months) neck pain with spontaneously painful, palpable (i.e., active) MTrPs and healthy volunteers without spontaneous pain (having palpably normal muscle tissue) were recruited for this study. The upper trapezius muscles in all subjects were imaged, and the echotexture was analyzed using entropy filtering of B-mode images. Vibration elastography was performed by vibrating the muscle externally at 100 Hz. Color Doppler variance imaging was used to quantify the regions of color deficit exhibiting low vibration amplitude. The imaging measures were compared against the clinical findings of a standardized physical exam. We found that sites with active MTrPs (n = 14) have significantly lower entropy (p < 0.05) and significantly larger nonvibrating regions (p < 0.05) during vibration elastography compared with normal, uninvolved muscle (n = 15). A combination of both entropy analysis and vibration elastography yielded 69% sensitivity and 81% specificity in discriminating active MTrPs from normal muscle. These results suggest that active MTrPs have more homogeneous texture and heterogeneous stiffness when compared with normal, unaffected muscle. Our methods enabled us to improve the imaging contrast between suspected MTrPs and surrounding muscle. Our results indicate that in subjects with chronic neck pain and active MTrPs, the abnormalities are not confined to discrete isolated nodules but instead affect the milieu of the muscle surrounding palpable MTrPs. With further refinement, ultrasound imaging can be a promising objective method for characterizing soft tissue abnormalities associated with active MTrPs and elucidating the role of MTrPs in the pathophysiology of MPS.